Variabilidade pluviométrica e a erosividade na unidade hidrográfica Pirapó, Paranapanema III e IV, Paraná - Terassi, Paulo Miguel de Bodas (2015)
The study of climatic features is of great importance when it comes to environmental management. Specifically, research concerning rainfall spatio - temporal behavior provides help to the planning of many sectors, while the knowledge of rainfall erosivity allows identifying areas and periods in which soil conservation measures are a priority. In this perspective, this research aims at studying rainfall variability as well as erosivity in Pirapó, Paranapanema III and IV hydrographic unit, which is located at the so-called Third Plateau of Paraná, between the 22º30'S and 23º30'S parallels and the 51º00'W and 53º00'W meridians. The rainfall data was collected from thirty five rain gauges at Paraná Water Institute and from five weather stations at Paraná Agronomy Institute (IAPAR), National Weather Institute (INMET) and Paraná Meteorological System (SIMEPAR). The data aforementioned were processed within the temporal segmentation 1976 to 2012, to the annual, seasonal, monthly and daily time scales. The descriptive statistics were applied to all the gauges according to the following parameters: average, maximum, minimum, standard deviation and coefficient of variation. The 'standard years technique', by Monteiro (1976), was used in order to identify the typically rainy and dry years. A methodology by Rufino, Biscaia and Merten (1993) was applied to determine the rainfall erosivity index. The Cluster Analysis technique, in turn, was used to identify the rainfall and erosivity predominant spatial standards to the annual and monthly time scales. The rainfall and erosivity index results were specialized through the isohyetal and isoerodent maps, which were developed with app Surfer 9.0. It was possible to verify that the most elevated sector of the hydrographic unit showed the greatest heights of rainfall, the biggest amount of rainy days and the greatest erosion potential. On the other hand, the sectors with the lowest altimetric quotas had the lowest results regarding rainfall, amount of rainy days and erosity. The 'standard years technique' enabled evaluating the changes of rainfall and erosivity characteristics to two rainy years and two dry ones. It was noticed that the results regarding rainfall, amount of rainy days and erosivity to the seasonal time scales were aligned to the results that had been verified and to the usual behavior of the regional atmospheric dynamics. It became known that the period from January to March and from September to December has the greatest rainfall average, the biggest amount of rainy days and the greatest erosion potential. The cluster analysis enabled identifying the annual and monthly features of rainfall, the amount of rainy days and the erosivity, as well as the relation of this parameter with the hypsometric characteristics to four homogenous groups.